2022
DOI: 10.3390/ijms23136993
|View full text |Cite
|
Sign up to set email alerts
|

miR-218-5p/RUNX2 Axis Positively Regulates Proliferation and Is Associated with Poor Prognosis in Cervical Cancer

Abstract: The overexpression of miR-218-5p in cervical cancer (CC) cell lines decreases migration, invasion and proliferation. The objective was to identify target genes of miR-218-5p and the signaling pathways and cellular processes that they regulate. The relationship between the expression of miR-218-5p and RUNX2 and overall survival in CC as well as the effect of the exogenous overexpression of miR-218-5p on the level of RUNX2 were analyzed. The target gene prediction of miR-218-5p was performed in TargetScan, miRTa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In a parallel investigation, Onodera et al scrutinized 137 cases of invasive ductal carcinoma of the breast through immunohistochemical staining and documented overexpression of RUNX2 [ 66 ]. Concurrently, elevated levels of RUNX2 in cervical cancer were found to be associated with decreased miR-218-5p expression, and this high expression of RUNX2 positively regulated cervical cancer cell proliferation [ 67 ].Wang et al found that MRE11 plays a pro-cancer role in oral cancer through the RUNX2/CXCR4/AKT/FOXA2 signaling axis, and both MRE1 and RUNX2 have been shown to be highly expressed in oral cancer samples [ 68 ]. Sancisi et al demonstrated that RUNX2 expression is reactivated in thyroid and breast cancers [ 69 ].…”
Section: Runx Proteins In the Landscape Of Cancer Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel investigation, Onodera et al scrutinized 137 cases of invasive ductal carcinoma of the breast through immunohistochemical staining and documented overexpression of RUNX2 [ 66 ]. Concurrently, elevated levels of RUNX2 in cervical cancer were found to be associated with decreased miR-218-5p expression, and this high expression of RUNX2 positively regulated cervical cancer cell proliferation [ 67 ].Wang et al found that MRE11 plays a pro-cancer role in oral cancer through the RUNX2/CXCR4/AKT/FOXA2 signaling axis, and both MRE1 and RUNX2 have been shown to be highly expressed in oral cancer samples [ 68 ]. Sancisi et al demonstrated that RUNX2 expression is reactivated in thyroid and breast cancers [ 69 ].…”
Section: Runx Proteins In the Landscape Of Cancer Expressionmentioning
confidence: 99%
“…Elevated levels of RUNX2 consistently serve as an adverse prognostic marker across multiple cancer types. For instance, in cervical cancer, high RUNX2 expression correlates with poor prognosis, and both RUNX2 and its inhibitory counterpart, miR-218-5p, are identified as potential prognostic markers [ 67 ]. Research by Li et al indicated that the upregulation of RUNX2 in EOC is likely associated with tumor progression and unfavorable outcomes [ 104 ].…”
Section: Prognostic Implications Of Runx Proteinsmentioning
confidence: 99%
“…Consistent results with these were obtained by Western blot analysis of 10 paired cancer and normal tissues [ 17 ]. RUNX2 protein was detected in cervical cancer tissues, and RUNX2 expression declined upon overexpression of miR-218-5p in C-33A and CaSki cells [ 58 ]. RUNX2 protein was elevated in human thyroid cancer cell lines and cancer tissues compared with primary cell lines and normal thyroid tissues [ 10 ].…”
Section: Runx2 Expression In Cancersmentioning
confidence: 99%